Transcutaneous electrical nerve stimulation reduces exercise-induced perceived pain and improves endurance exercise performance - Astokorki, A. H.; Mauger, A. R. (European Journal of Applied Physiology, 2017)
Purpose: Muscle pain is a natural consequence of intense and prolonged exercise and has been suggested to be a limiter of performance. Transcutaneous electrical nerve stimulation (TENS) and interferential current (IFC) have been shown to reduce both chronic and acute pain in a variety of conditions. This study sought to ascertain whether TENS and IFC could reduce exercise-induced pain (EIP) and whether this would affect exercise performance. It was hypothesised that TENS and IFC would reduce EIP and result in an improved exercise performance. Methods: In two parts, 18 (Part I) and 22 (Part II) healthy male and female participants completed an isometric contraction of the dominant bicep until exhaustion (Part I) and a 16.1 km cycling time trial as quickly as they could (Part II) whilst receiving TENS, IFC, and a SHAM placebo in a repeated measures, randomised cross-over, and placebo-controlled design. Perceived EIP was recorded in both tasks using a validated subjective scale. Results: In Part I, TENS significantly reduced perceived EIP (mean reduction of 12%) during the isometric contraction (P = 0.006) and significantly improved participants` time to exhaustion by a mean of 38% (P = 0.02). In Part II, TENS significantly improved (P = 0.003) participants` time trial completion time (~2% improvement) through an increased mean power output. Conclusion: These findings demonstrate that TENS can attenuate perceived EIP in a healthy population and that doing so significantly improves endurance performance in both submaximal isometric single limb exercise and whole-body dynamic exercise.